The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1071/en11016
|View full text |Cite
|
Sign up to set email alerts
|

Humic Ion-Binding Model VII: a revised parameterisation of cation-binding by humic substances

Abstract: Article (refereed) -postprintTipping, E.; Lofts, S.; Sonke, J.E.. 2011. Humic Ion-Binding Model VII: a revised parameterisation of cation-binding by humic substances. Environmental Chemistry, 8 (3). 225-235. 10.1071/EN11016Contact CEH NORA team at noraceh@ceh.ac.ukThe NERC and CEH trademarks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other countries, and may not be used without the prior written consent of the Trademark owner. [1,2] incorporating Humic Ion-Binding Model 55 V … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
317
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 361 publications
(327 citation statements)
references
References 67 publications
2
317
0
Order By: Relevance
“…We have previously performed three such studies focussing on data from fresh waters, [14] estuarine and coastal waters [15] and the open ocean, [16] and comparing them with predictions obtained using WHAM6 [17] or WHAM7. [18] We found that measurements and model predictions based only on metal binding by humic-type ligands (i.e. DOM) were in broad agreement, but in many cases differences were greater than could be explained by data uncertainty, and there was a tendency for the differences to be larger at low metal concentrations.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…We have previously performed three such studies focussing on data from fresh waters, [14] estuarine and coastal waters [15] and the open ocean, [16] and comparing them with predictions obtained using WHAM6 [17] or WHAM7. [18] We found that measurements and model predictions based only on metal binding by humic-type ligands (i.e. DOM) were in broad agreement, but in many cases differences were greater than could be explained by data uncertainty, and there was a tendency for the differences to be larger at low metal concentrations.…”
Section: Introductionmentioning
confidence: 69%
“…The data set is summarised in Tables 1 and S1, with further details in references. [14][15][16] Chemical speciation modelling We used WHAM [10] incorporating Humic Ion-Binding Model VII [18] to perform the speciation calculations; previously, the open-ocean calculations [16] were done using Model VI. [17] Models VI and VII use structured formulations of discrete, chemically plausible binding sites for protons in humic and fulvic acids (HA, FA), in order to allow the creation of regular arrays of bidentate and tridentate binding sites for metals.…”
Section: The Data Setmentioning
confidence: 99%
See 1 more Smart Citation
“…Speciation of soil pore waters To assess the potential toxicity of the metals in the centrifuged pore waters on soil biota we compared free ion concentrations obtained using WHAM 7 21 against the 'critical limits' published by Lofts et al 18 and de Vries et al 19 . Input data to WHAM 7 40 included solution pH, temperature (277 K) and solution concentrations of Na, Mg, Al, K, Ca, Fe(III), Mn, Ni, Cu, Zn, Cd, Pb, Cl -, NO 3 -, SO 4 2-, CO 3 2-, F -and PO 4 3-.…”
mentioning
confidence: 99%
“…In the present study, WHAM VII was used for modelling metal accumulation in 135 plant roots (Tipping, 1994;Tipping et al, 2011). In WHAM, metal sorption to humic 136 substances is simulated by using a structured formulation of discrete, chemically-137 simultaneously because the data were generated in mixture exposures.…”
Section: Bioaccumulation Modelling 134mentioning
confidence: 99%